Delivering The Hydrogen Economy - MAXIMILLIAN NEWBERRY (2022)
Hydrogen can be burned as a heating fuel and used to generate electricity with fuel cells. Hydrogen can be stored and transported in a variety of methods, primarily as a compressed gas (CGH2) or as a cryogenic liquid (LH2). CGH2 was found to be the most economic form of hydrogen storage when utilising pressure vessels, has the lowest storage energy penalty, and exhibits long term and geological storage capabilities. LH2 was found to be more economical for transportation via road and rail, and to achieve the highest gravimetric and volumetric energy densities.Hydrogen storage systems were found to achieve gravimetric storage densities of up to 1490 Wh/kg, far exceeding lithium-ion cell densities of 243 Wh/kg. This along with long term storage capabilities makes hydrogen preferable for decarbon-ising off-grid heating, large scale mobility electriﬁcation and aviation. Hydrogen is also essential for decarbonising the steel industry.Hydrogen produced from steam-methane reforming with carbon capture (blue hydrogen) was found to insufﬁciently reduce greenhouse gas emissions, therefore, hydrogen produced from water splitting using renewable energy (green hydrogen) and nuclear power (pink hydrogen) were assumed to be the key methods of hydro-gen production in future infrastructure.Comparisons between on-site production, container swap and static tanks utilis-ing the reﬁll method were found to all have important beneﬁts and drawbacks thus underlining the need for all systems in the emerging green hydrogen economy.Understanding the speciﬁc pros and cons of each storage and transportation method lead to the conclusion that both CGH2 and LH2 along with type 1, 2, 3, 4 and cryogenic vessels are likely to all be required in speciﬁc scenarios with an em-phasis on the need for low cost mobile pressure vessels using the container swap method and the development of a mobile LH2 to static CGH2 reﬁll infrastructure.